2016
DOI: 10.6007/ijarbss/v5-i12/1962
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Strategic Human Resource Management on Firm Performance of Jordan’s Corporate Organizations

Abstract: This paper investigate the extent to which Strategic Human Resource Management (SHRM) influences Firm Performance. Quick environmental changes, competition to extend innovative products, changing customer and angel demands and globalization have become the criterion backdrop for firms. Sustained Competitive Advantage (CA) could be generated from a firm's Human Capital by styling SHRM to diagnose a firm's strategic needs which is wanted to implement a CA and achieve operational goals. Effective Human Resource M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This result indicates that HRM practices are the most important determinant of OP. These results are in line with the findings of previous studies (Alkhazali et al, 2017;Katou & Budhwar 2015;Alkhazali & Mohd, 2015;Maruf & Raheem, 2014;Almazari, 2014;Nigam et al, 2011). This study demonstrates that it would be in the best interest of commercial sampled banks in particular, to apply a relationship management approach in the delivery of their services and workforce strategies in light of the employee performance challenges currently facing the sector.…”
Section: The Relationship Between Hrm Practices and Organizational Pe...supporting
confidence: 91%
See 1 more Smart Citation
“…This result indicates that HRM practices are the most important determinant of OP. These results are in line with the findings of previous studies (Alkhazali et al, 2017;Katou & Budhwar 2015;Alkhazali & Mohd, 2015;Maruf & Raheem, 2014;Almazari, 2014;Nigam et al, 2011). This study demonstrates that it would be in the best interest of commercial sampled banks in particular, to apply a relationship management approach in the delivery of their services and workforce strategies in light of the employee performance challenges currently facing the sector.…”
Section: The Relationship Between Hrm Practices and Organizational Pe...supporting
confidence: 91%
“…Current research in the field of OP and HRM has gone beyond testing for the relationship between the two, to instead focusing on the mechanisms by which HRM practices influence OP (Moideenkutty et al, 2012;Collins & Smith, 2006). However, some commentators have questioned the methodological rigor of these studies (Alkhazali & Mohd, 2015;Katou & Budhwar 2015;Moideenkutty et al, 2012), and suggest that it is premature to assume an unequivocal positive relationship between HRM practices and OP, and supports the view that further research is needed using more rigorous research designs and approaches Alkhazali et al, (2019) has proposed two different HR practices frameworks for acceptable OP. This is a development framework and an internal acquisition framework.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Atteya (2012) examined the effect of HRM practices on job performance in Egypt's petroleum industry, revealing a significant positive impact. Loo & Beh (2013) studied the link between strategic HRM practices and organizational performance in Malaysian insurance companies, identifying performance reviews, internal communication, and SHRM alignment as key indicators. Al-Bahussin & El-Garaihy (2013) found that HRM techniques positively influence organizational culture, knowledge management, innovation, and performance in Saudi Arabian businesses.…”
Section: Effectiveness Of Human Resource Managementsmentioning
confidence: 99%
“…advantage. Human resources with advanced capabilities, high motivation, and a good working environment will perform better (Katou & Budhwar, 2007;Waiganjo et al, 2012). The insurance industry, a service sector that relies on its workforce, will gain from enhanced performance, competitive advantage, and sustainable growth.…”
Section: Claims Management and Firm Performance Of Insurance Companie...mentioning
confidence: 99%